A preparation method of guanine nanotube / vermiculite-phosphorylated nanocellulose composite material and its application in humidity sensor

By preparing guanine nanotube/vermiculite composite materials under the vermiculite confined space and introducing phosphorylated nanocellulose, the shortcomings of existing humidity sensor materials in humidity sensing performance are solved, and high-strength flexible network and excellent The composite structure of proton/ion conduction capability significantly improves the detection accuracy and response speed of the humidity sensor.

CN116794119BActive Publication Date: 2025-02-11FUJIAN AGRI & FORESTRY UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310867654.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-15
Publication Date
2025-02-11
Estimated Expiration
2043-07-15

AI Technical Summary

Technical Problem

The existing humidity sensor materials have shortcomings in humidity sensing performance, making it difficult to achieve rapid response and high-accuracy humidity detection.

Method used

Guanine nanotube/vermiculite composite materials were prepared in the confined space of vermiculite by one-step pyrolysis method, and phosphorylated nanocellulose was introduced, and guanine nanotube/vermiculite-phosphorylated nanofibers were prepared by vacuum-assisted self-assembly method. Cinal composite membranes (G/VMT-PCNCs) are used to build a composite structure with high-strength flexible network and excellent proton/ion conduction capability.

Benefits of technology

It has realized the construction of a composite structure with high-strength flexible network and excellent proton/ion conduction capabilities, significantly improving the humidity sensing performance of the humidity sensor, and having fast response and high accuracy detection capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116794119B_ABST
    Figure CN116794119B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing a guanine nanotube / vermiculite-phosphorylated nanocellulose composite material and its application in a humidity sensor. With guanine as a precursor, under the spatial restriction of two-dimensional vermiculite nanosheets, ultra-thin nanosheet guanine self-assembles into nanotubes with a hollow structure through a simple pyrolysis reaction. The prepared guanine nanotube / vermiculite two-dimensional composite material has the advantages of controllable pore structure and multiple gas adsorption sites, which is beneficial to the adsorption and desorption of water molecules and can improve the humidity sensing performance of traditional sensitive membranes. The process adopted by the present invention is simple, low-cost, and suitable for mass production. As a humidity-sensitive material, the invented guanine nanotube / vermiculite two-dimensional composite material has humidity-sensitive characteristics of short response time, small hysteresis and good repeatability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of composite material preparation, and in particular relates to a guanine nanotube / vermiculite-phosphorylated nanocellulose composite material and a preparation method thereof and application of the composite material in a humidity sensor. Background Art

[0002] Faced with the strong constraints of resources, energy and ecological environment, the task of green and safe development of advanced functional materials has become more urgent. In recent years, scientists have attached unprecedented importance to the discovery of sustainable resource substitutes, and have conducted in-depth research on biomass from plants and microorganisms. Carbon-based materials are material systems with carbon atoms as the skeleton, including pure carbon systems such as diamond and graphite and multi-atom systems such as silicon carbide and polymer organic matter. They have attracted much attention due to their rich structural morphology and excellent mechanical, electrical, thermodynamic and other properties. Carbon nanomaterials have also received widespread attention in promoting proton conduction.

[0003] The present invention adopts a one-step pyrolysis method and uses guanine as a precursor to prepare a "sandwich" structured guanine nanotube / vermiculite composite material in the confined space of vermiculite. Further, by introducing phosphorylated nanocellulose, a vacuum-assisted self-assembly method is used to prepare a guanine nanotube / vermiculite-phosphorylated nanocellulose composite membrane (G / VMT-PCNCs), in order to construct a one-dimensional / two-dimensional composite structure with a high-strength flexible network rich in active sites and excellent proton / ion conductivity. Summary of the invention

[0004] The purpose of the present invention is to provide a guanine nanotube / vermiculite-phosphorylated nanocellulose composite material and a preparation method thereof and application of the composite material in a humidity sensor.

[0005] To achieve the above object, the present invention adopts the following technical solution:

[0006] A method for preparing a guanine nanotube / vermiculite-phosphorylated nanocellulose (G / VMT-PCNCs) composite material comprises the following steps:

[0007] (1) Preparation of guanine nanotube / vermiculite ultrathin carbon nanosheets (G / VMT)

[0008] 1.1 Raw material pretreatment

[0009] The raw vermiculite particles were ground and sieved to a particle size of 30-60 mesh, and then immersed in a hydrogen peroxide solution for 12-48 h. After filtering out the excess hydrogen peroxide solution, the vermiculite was heated in a microwave oven for 90 s.

[0010] 1.2 Preparation of guanine nanotube / vermiculite ultrathin carbon nanosheets

[0011] 0.5 g of pretreated vermiculite and 4.0 g of guanine were added to 50 mL of ultrapure water, mechanically stirred and mixed at 80 °C for 48 h, and then dried at 60 °C to obtain a mixture of pre-expanded vermiculite and guanine; the mixture was placed in a tube furnace, and under nitrogen protection, the mixture was heated from room temperature to 500-900 °C at a heating rate of 5 °C / min, and kept in the tube furnace for 1 h. After cooling to room temperature, the obtained guanine nanotubes / vermiculite ultrathin carbon nanosheets were ground into powder;

[0012] (2) Preparation of guanine nanotube / vermiculite-phosphorylated nanocellulose composite membrane

[0013] 3 g of microcrystalline cellulose and 24 g of urea were added to 16 g of phosphoric acid solution, and ultrasonicated at 80 °C for 5 h. The mixture was centrifuged at 11000 r / min for 15 min, the supernatant was removed, and the mixture was placed in a 150 °C oven for 25 min. Ultrapure water was added and the mixture was centrifuged at 10000 r / min for 10 min. After repeated centrifugation and washing for 3 times, the pH was adjusted to 12, and ultrasonicated at 80 °C for 4 h. Finally, the obtained phosphorylated nanocellulose suspension was dialyzed with ultrapure water until the pH reached neutrality and diluted to 0.5 mg / mL.

[0014] 5 mg of guanine nanotubes / vermiculite ultrathin carbon nanosheets were added to 0.1-0.4 mL of PCNCs suspension, then diluted to 100 mL with ultrapure water, filtered onto a 0.22 μm pore size polyethersulfone membrane under vacuum, and dried in an oven at 60 °C for 24 h to obtain a guanine nanotube / vermiculite-phosphorylated nanocellulose composite membrane.

[0015] Furthermore, the concentration of the hydrogen peroxide solution in step (1) is 30 wt %.

[0016] Furthermore, the concentration of the phosphoric acid solution in step (2) is 85 wt%.

[0017] Application: Application of guanine nanotube / vermiculite-phosphorylated nanocellulose composite membrane as humidity sensitive material in humidity sensor.

[0018] The advantages of the present invention are:

[0019] (1) By utilizing the layered porous structure of vermiculite and the spatial confinement between the layers, guanine molecules self-assemble in the confined space of the vermiculite layers to form a unique nanotubular structure. The one-dimensional guanine nanotube structure is conducive to the rapid and long-distance transfer of molecules and ions, and the vermiculite nanosheets contribute to in-plane conduction. The prepared guanine nanotube / vermiculite two-dimensional composite material has the advantages of controllable pore structure, multiple gas adsorption sites, and good device integration compatibility, which can improve the humidity sensing performance of traditional sensitive membranes.

[0020] (2) Creating excellent humidity-sensitive materials plays an important role in the development of high-performance gas sensors. The tetrahedral crystals of vermiculite, a natural resource, have abundant negative charges, good hygroscopicity and stability. By utilizing the two-dimensional layered structure of vermiculite itself, guanine from biomass extract self-assembles into a nanotube structure in the confined space of the vermiculite layer. The two-dimensional nanocomposite sensitive membrane material formed can not only provide abundant sensing active sites, but also facilitate the adsorption and desorption of water molecules due to its pore and channel structure, thereby improving the sensing performance of traditional sensitive membranes. The process used in the invention is simple, low-cost, suitable for mass production, and has excellent rapid response recovery characteristics. Therefore, it has important application value in accurate and reliable humidity sensing detection.

[0021] (3) Using two-dimensional nanosheet materials to stack and construct long-range ordered molecular and ion transport channels is an effective strategy for ion and proton conduction. Guanine has hydrogen bond donors and acceptors, and can self-assemble through hydrogen bonds and rearrange on the two-dimensional plane. Vermiculite, as a layered porous structure, has a physical confinement effect between the sheets, and can serve as a "microreactor" for guanine, helping guanine to form ultra-thin two-dimensional nanosheets and hollow nanotubes. By adjusting the interlayer spacing of vermiculite sheets, the morphology of guanine can be controlled. However, the adhesion between adjacent vermiculite and carbonized guanine is relatively weak, and the rigidity of vermiculite is relatively strong. It is difficult for pure guanine and vermiculite to form an elastic three-dimensional network structure. The high aspect ratio of nanocellulose gives it a large specific surface area and an overall low density. The rich surface functional groups can provide a variety of possibilities for its chemical modification, thereby providing more sites for the cross-linking of structural units and improving mechanical properties. Therefore, nanocellulose is suitable for constructing flexible and lightweight networks. The present invention introduces nanocellulose into lamellar guanine and vermiculite to assist in cross-linking the lamellar structure, and is expected to form a two-dimensional film with high conductivity. As a proton donor and acceptor, the phosphate group has amphoteric conductivity and can form a dynamic hydrogen bond network, so that protons can jump from one group to another through the network. In addition, the phosphate group also has a large polarizability and hydration energy, and can form hydrogen bonds with water. Therefore, the addition of phosphorylated nanocellulose can improve the proton conductivity of the material and improve the humidity sensing performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 (a) Proton conductivity variation curve of G / VMT composite membrane at different pyrolysis temperatures before and after immersion in ultrapure water, (b) Proton conductivity variation curve of G / VMT composite membrane at different pyrolysis temperatures with relative humidity, (c) Proton conductivity variation curve of G / VMT-900 and G / VMT-PCNCs composite membrane with temperature, (d) Proton conductivity variation curve of G / VMT-PCNCs composite membrane with relative humidity;

[0023] Figure 2 FTIR spectra of (a) VMT-0(24), G-0, G / VMT-600(24), G / VMT-700(24), G / VMT-800(24) and G / VMT-900(24), (b) G / VMT-PCNCs-0.1, G / VMT-PCNCs-0.2,

[0024] FTIR spectra of G / VMT-PCNCs-0.3 and G / VMT-PCNCs-0.4;

[0025] Figure 3 XPS spectra of (a) G / VMT-600, G / VMT-700, G / VMT-800, and G / VMT-900, high-resolution XPS spectra of (b) C1 s, (c) N1s, (d) O1 s, and (e) Si2 p;

[0026] Figure 4 The full XPS spectra of G / VMT-PCNCs-0.1, G / VMT-PCNCs-0.2, G / VMT-PCNCs-0.3, G / VMT-PCNCs-0.4 and PCNCs;

[0027] Figure 5 (a) XRD patterns of G-0, G-900, VMT-0(24), VMT-900(24) and G / VMT-900(24), (b) XRD patterns of PCNCs, G / VMT-PCNCs-0.1, G / VMT / PCNCs-0.2, G / VMT-PCNCs-0.3, G / VMT-PCNCs-0.4;

[0028] Figure 6 FESEM images of VMT original, G-900, G / VMT-600 (12), G / VMT-700 (12), G / VMT-800 (12), G / VMT-900 (12), G / VMT-900 (24), G / VMT-900 (36) and G / VMT-900 (48);

[0029] Figure 7(a) G / VMT-PCNCs-0.1, (b) G / VMT-PCNCs-0.2, (c) G / VMT-PCNCs-0.3, (d) G / VMT-PCNCs-0.4, (e) guanine nanotubes confined in vermiculite, (f) FESEM images of broken vermiculite sheets;

[0030] Figure 8 (a) 200nm TEM image of G / VMT-PCNCs-0.1, (b) 100nm TEM image of G / VMT-PCNCs-0.1, (c) AFM images of VMT-900, (d) G / VMT-900, (e) PCNCs, and (f) G / VMT-PCNCs-0.1;

[0031] Fig. 9 Contact angle diagrams of G / VMT-PCNCs-0.1, G / VMT-PCNCs-0.2, G / VMT-PCNCs-0.3 and G / VMT-PCNCs-0.4. DETAILED DESCRIPTION

[0032] In order to make the above features and advantages of the present invention more clearly understood, the following embodiments are given for detailed description. The methods of the present invention are all conventional methods in the art unless otherwise specified.

[0033] 1. Material preparation

[0034] 1.1 Preparation of guanine nanotube / vermiculite ultrathin carbon nanosheets

[0035] (1) Raw material pretreatment

[0036] The raw vermiculite particles were ground and sieved to a particle size of 30-60 mesh (250-550 μm), and then immersed in 40 mL of 30wt% hydrogen peroxide solution for 12 h, 24 h, 36 h and 48 h. After filtering out the excess hydrogen peroxide solution, the vermiculite was heated in a microwave oven for 90 s.

[0037] During the heating process, the gas produced by the decomposition of the adsorbed hydrogen peroxide and the water molecules evaporate between the vermiculite layers, making the space between the vermiculite layers larger, which is conducive to the entry of guanine molecules into the interior of the vermiculite layers.

[0038] (2) Preparation of guanine nanotube / vermiculite ultrathin carbon nanosheets

[0039] 0.5 g of pretreated vermiculite and 4.0 g of guanine were added to 50 mL of ultrapure water, mechanically stirred and mixed at 80 °C for 48 h, and then dried at 60 °C to obtain a mixture of pre-expanded vermiculite and guanine. The mixture was placed in a tube furnace and heated from room temperature to 500 °C, 600 °C, 700 °C, 800 °C and 900 °C at a heating rate of 5 °C / min under nitrogen protection, and kept in the tube furnace for 1 h. After cooling to room temperature, the obtained guanine nanotubes / vermiculite ultrathin carbon nanosheets were ground into powders and marked as G / VMT-X(Y) (X=600, 700, 800, 900, Y=12, 24, 36, 48) according to the pyrolysis temperature and hydrogen peroxide pretreatment time.

[0040] (3) Control experiment

[0041] For comparison, pure guanine pyrolysis nanosheets without the addition of thermally expanded vermiculite were synthesized by the same process and labeled as GX (X=0, 600, 700, 800, 900); pure vermiculite without the addition of guanine was synthesized by the same process and labeled as VMT-X(Y) (X=600, 700, 800, 900, Y=12, 24, 36, 48).

[0042] 1.2 Preparation of guanine nanotube / vermiculite-phosphorylated nanocellulose composite membrane

[0043] Preparation of phosphorylated nanocellulose (PCNCs): 3 g of microcrystalline cellulose and 24 g of urea were added to 16 g of 85wt% phosphoric acid solution, ultrasonicated at 80 °C for 5 h, centrifuged the mixture at 11000 r / min for 15 min, removed the supernatant, and placed in a 150 °C oven for 25 min. Ultrapure water was then added and centrifuged at 10000 r / min for 10 min. After repeated centrifugation and washing for 3 times, the pH was adjusted to 12, ultrasonicated at 80 °C for 4 h, and finally the obtained PCNCs suspension was dialyzed with ultrapure water until the pH reached neutral and diluted to 0.5 mg / mL.

[0044] 5 mg of G / VMT-900(24) was added to 0.1, 0.2, 0.3 and 0.4 mL of PCNCs suspension, then diluted to 100 mL with ultrapure water, filtered onto a 0.22 μm pore size polyethersulfone membrane under vacuum, and dried in an oven at 60 °C for 24 h to obtain G / VMT-PCNCs composite membranes. The materials were labeled as G / VMT-PCNCs-0.1, G / VMT-PCNCs-0.2, G / VMT-PCNCs-0.3, and G / VMT-PCNCs-0.4, respectively. G / VMT-600(24), G / VMT-700(24), G / VMT-800(24), G / VMT-900(24) and PCNCs control group were prepared in the same way.

[0045] 1.3 Construction of the proton conduction device

[0046] VC4092A (Victory) LCR digital bridge tests proton conductivity. The specific test method is as follows:

[0047] (1) Testing the proton conductivity of different phosphorylated nanocellulose / guanine / vermiculite composite membranes: The membranes were cut into strips of 10 mm × 20 mm and placed between two electrodes. The resistance value was measured by the above test device in a dry state. The membranes were then immersed in ultrapure water for 10 min and the resistance value was measured again.

[0048] (2) Testing the proton conductivity under different humidity conditions: The membrane was cut into strips of 10 mm × 20 mm and placed between two electrodes. The test device was placed in a closed container containing different saturated salt solutions providing 11% RH, 33% RH, 43% RH, 54% RH, 75% RH, 84% RH and 97% RH. The resistance value was tested at 25 °C with an equilibrium time of 30 min.

[0049] (3) Testing the proton conductivity at different temperatures: The membrane was cut into strips of 10 mm × 20 mm and placed between two electrodes. The test device was placed on an intelligent digital display magnetic stirring heating plate at 97% RH. The resistance value was tested at 20 ℃, 30 ℃, 40 ℃, 50 ℃, 60 ℃, 70 ℃ and 80 ℃. The equilibrium time was 30 min.

[0050] 2 Results and Discussion

[0051] 2.1 Study on the proton transfer behavior of guanine nanosheets and their composites

[0052] In this work, the proton transfer behavior of G / VMT-600, G / VMT-700, G / VMT-800, G / VMT-900 and G / VMT-PCNCs was studied by using a bridge. The optimal pyrolysis temperature was determined by comparing the changes in proton conductivity of G / VMT with different pyrolysis temperatures before and after immersion in ultrapure water. The proton conductivity of G / VMT-600, G / VMT-700, G / VMT-800 and G / VMT-900 was calculated based on the resistance. Figure 1 Figure a shows the proton conductivity of G / VMT-600, G / VMT-700, G / VMT-800, and G / VMT-900 before and after immersion in ultrapure water. At 25 °C, the proton conductivity of the G-VMT membrane increases with the increase in pyrolysis temperature, and the proton conductivity is the highest (2.3 mS / cm) at G / VMT-900. For G / VMT-600, G / VMT-700, G / VMT-800, and G / VMT-900 membranes, the proton conductivity after immersion in ultrapure water is higher than that before immersion in ultrapure water, indicating that after the humidity increases, the adsorbed water molecules participate in proton conduction. Figure 1 Figure b shows the changes in proton conductivity of G / VMT-600, G / VMT-700, G / VMT-800, and G / VMT-900 at 25°C and relative humidity of 11-97%. As the relative humidity increases, the proton conductivity increases, which once again proves that the increase in humidity prompts the adsorption of more water molecules and promotes proton conduction.

[0053] The changes in proton conductivity of G / VMT-900, G / VMT-PCNCs-0.1, G / VMT-PCNCs-0.2, G / VMT-PCNCs-0.3, and G / VMT-PCNCs-0.4 at different temperatures and humidities were further investigated. Figure 1 As shown in cd. At 97% relative humidity, the proton conductivity of all materials showed an upward trend with increasing temperature, indicating that the transfer of water molecules in G / VMT-PCNCs and G / VMT-900 is a heat-promoted process. Among them, the proton conductivity of G / VMT-PCNCs-0.2 is the largest at 80 °C (1.15 mS / cm), and the error of G / VMT-PCNCs is smaller than that of G / VMT-900. At 25 °C, as the relative humidity increases from 11% to 97%, the proton conductivity of G / VMT-PCNCs shows an upward trend.

[0054] 2.2 Surface chemical structure analysis

[0055] Figure 2The infrared absorption spectrum of a shows that the characteristic peaks of guanine molecules and vermiculite appear in the infrared spectrum of the composite material, indicating that the guanine molecules have successfully entered the interlayer of vermiculite. -1 The absorption peak at 1684 cm is attributed to the stretching vibration of -NH and -OH. -1 The absorption peak at 1260 cm-1 is attributed to the stretching vibration of the C=N double bond. -1 、1379 cm -1 and 1416 cm -1 The absorption peak at 1690-1500 cm -1 and 1220-1000 cm -1 The absorption peak is related to the stretching vibration of C=C and C=O, located at 877 cm -1 and 848 cm -1 The absorption peak of 3500cm is the breathing vibration of the triazine ring. As the pyrolysis temperature increases, it is found that some active functional groups are released, and some nitrogen elements exist in the reorganized carbon system in a stable structure such as CN. For vermiculite, 3500cm -1 and 1600 cm -1 The absorption peak at 1010 cm is attributed to the stretching vibration of -OH of interlayer adsorbed water molecules; -1 The strong absorption peak at 686 cm-1 is attributed to the stretching vibration of Si-O tetrahedron in vermiculite; -1 The absorption peak is the bending vibration of Mg-O-Si.

[0056] Figure 2 b is the infrared absorption spectra of G / VMT-PCNCs-0.1, G / VMT-PCNCs-0.2, G / VMT-PCNCs-0.3, and G / VMT-PCNCs-0.4. All samples have an infrared absorption spectrum of 3352 cm -1 There are stretching vibration peaks attributed to -OH near 1311cm -1 The peaks near the cellulose absorbance peak are at 1053 cm −1 and 881 cm −1 The CO stretching of cellulose and the glycosidic connection between sugar units in cellulose are located at 975 cm −1 and 814 cm −1 The absorption peaks at represent the stretching modes of P-OH and POC, which are superimposed on G / VMT-900 (24) and appear as broadened peaks observed in the experiment. The above results confirm the successful synthesis of G / VMT-PCNCs composites.

[0057] In order to study the chemical state of the elements and the surface chemistry of the material, XPS test analysis was carried out on the material. Figure 3 In the figure a, the full spectra of G / VMT-600, G / VMT-700, G / VMT-800, G / VMT-900, G-0 and VMT-0 are shown. In the full XPS spectrum of VMT-0, the characteristic peaks at 73.8, 102.07, 531.37, 1071.68 and 1303.00 eV are attributed to Al2 p, Si2 p, O1 s, Na1 s, and Mg1 s, respectively. In the full XPS spectrum of G-0, the characteristic peaks are at 285.94, 399.15 and 532.46 eV, which are attributed to C1 s, N1 s and O1 s, respectively. Figure 3 b, c, d, and e are high-resolution fitting diagrams of G / VMT-600, G / VMT-700, G / VMT-800, and G / VMT-900, respectively. Figure 3 In b), it can be seen that as the temperature increases, the NC=N content at 286.9 eV decreases, confirming that the increase in pyrolysis temperature releases some active functional groups. The carbon element in G / VMT-600, G / VMT-700, G / VMT-800, and G / VMT-900 exists mainly in the form of CC (284.8 eV), CO (286.1 eV), and NC=N (286.9 eV); N1 s spectrum ( Figure 3 c) can be divided into four types: pyridinic nitrogen (398.7 eV), pyrrolic nitrogen (399.9 eV), graphitic nitrogen (401.2 eV) and oxidized nitrogen (403.0 eV). As the temperature increases, the content of graphitic nitrogen that gives the carbon material high conductivity increases, while the content of pyrrolic nitrogen and oxidized nitrogen also decreases, which also indicates the loss of some active functional groups and the possible decrease in the degree of protonation. O1 s spectrum ( Figure 3 (d) shows that the oxygen element in G / VMT-600, G / VMT-700, G / VMT-800, and G / VMT-900 exists mainly in the form of CO (532.7 eV), Si-O-Si (531.6 eV), and C=O (530.8 eV); while the Si2 p spectrum ( Figure 3 Middle (e) is mainly composed of Si-N (102.1 eV), Si-C (103.0 eV) and Si-O (103.9 eV).

[0058] Figure 4The XPS spectra of PCNCs and G / VMT-PCNCs composites and PCNCs are shown. In the full spectrum of PCNCs, the characteristic peaks appear at 133.33, 285.94, 532.46 and 1071.68 eV, respectively, which are attributed to P2 p, C1 s, O1 s and Na1 s peaks, respectively. The presence of phosphorus confirms that the phosphate group is successfully grafted onto the nanocellulose. A small amount of Na element on the surface leads to residual Na on the fiber surface during the alkali treatment. + The addition of PCNCs increases the C and O element contents of the G / VMT-PCNCs composites. The increase in chemical bonds related to oxygen is beneficial to improving the hydrophilicity of the nanocomposites, thereby improving the sensitivity of the humidity sensor.

[0059] 2.3 Crystal structure analysis

[0060] XRD test further analyzed the microstructure of pyrolyzed guanine, such as Figure 5 As shown in a. In the guanine sample pyrolyzed at 900 °C, an obvious diffraction peak appeared at 2θ = 26°, corresponding to the (002) plane of graphitized carbon, while other characteristic peaks belonging to guanine disappeared. For vermiculite, a typical mica diffraction peak was observed at 2θ = 26.4°, and the characteristic peaks at 8-9° illustrate the ordered layered structure of vermiculite. In the spectrum of G / VMT-900(24), the characteristic peaks of guanine and vermiculite both showed a trend of weakening peak intensity. On the one hand, this may be due to the interlayer restriction of vermiculite, which reduces the size of guanine sheets. This result is consistent with the SEM performance. On the other hand, due to the graphitization of the material at high temperature and poor crystallinity, the weak peaks cover each other to form broad diffraction peaks.

[0061] Figure 5 Figure b shows the XRD diffraction patterns of PCNCs, G / VMT-PCNCs-0.1, G / VMT-PCNCs-0.2, G / VMT-PCNCs-0.3, and G / VMT-PCNCs-0.4. There are main peaks at around 16.5°, 22.5°, and 34.6°, corresponding to the diffraction planes of (110), (200), and (004), respectively, which are the characteristic crystal planes of cellulose type I. Generally speaking, the larger the size of the crystal, the narrower the diffraction peak. The characteristic peak of PCNCs is sharp, indicating that the prepared PCNCs have a good crystal structure and have a great influence on the mechanical properties of the material. The crystallinity of all samples was calculated using MDI Jade software. The crystallinity of PCNCs and G / VMT-PCNCs-0.1, G / VMT-PCNCs-0.2, G / VMT-PCNCs-0.3, and G / VMT-PCNCs-0.4 were 40.26%, 81.24%, 61.96%, 68.08%, and 73.05%, respectively.

[0062] 2.4 Morphological and structural analysis

[0063] The morphology and microstructure of the samples were studied using a field emission scanning electron microscope. Natural vermiculite has a layered structure with narrow interlayer space. After pretreatment, the interlayer spacing of vermiculite will expand with the extension of hydrogen peroxide immersion time. In this chapter, guanine after pyrolysis treatment presents a continuous sheet structure, and in the confined space of vermiculite nanosheets, guanine nanosheets can self-assemble into nanotubes with a special hollow structure.

[0064] like Figure 6 As shown in the figure, pyrolysis of guanine (G-900) at 900 °C presents nanosheets with a larger area. From the field emission scanning electron micrographs of G / VMT-600(12), G / VMT-700(12), G / VMT-800(12) and G / VMT-900(12), it can be seen that after guanine enters the confined space of the vermiculite layer, the size of the formed guanine nanosheets becomes smaller, and at the same time, some of them curl up into hollow nanotubes. G / VMT-900(12) has more nanotubes than the products at other temperatures. This may be because the increase in temperature causes guanine to gradually form two-dimensional nanosheets, but due to the small interlayer space of vermiculite, relatively less guanine enters the interlayer space.

[0065] The interlayer spacing of natural vermiculite is small, and different hydrogen peroxide immersion times can affect the interlayer spacing of vermiculite flakes. In order to explore the effect of different interlayer space sizes on the structure of guanine, pre-expanded vermiculite treated with hydrogen peroxide solution for 12 h, 24 h, 36 h and 48 h was used as a confined hard template. As the treatment time increases, the interlayer spacing of vermiculite increases. The FESEM image of G / VMT-900 (12) shows that due to the small interlayer spacing of vermiculite flakes, less guanine enters the interlayer of vermiculite, and only a small amount of interlayer nanotubular samples is distributed. In contrast, more one-dimensional nanotubular guanine and a small amount of two-dimensional sheet guanine appear between the layers of G / VMT-900 (24). However, as the interlayer spacing of vermiculite continues to increase, the one-dimensional nanotubular guanine of G / VMT-900 (36) and G / VMT-900 (48) decreases, while the two-dimensional sheet guanine increases, and as the space increases, the size of the two-dimensional sheet guanine increases. The formation of one-dimensional nanotubes may be due to the fact that the narrow space of vermiculite limits the planar size and thickness of guanine, and the ultrathin nanosheet guanine automatically curls up into a tube.

[0066] At the same time, the morphology and structure of G / VMT-PCNCs samples were studied using field emission scanning electron microscopy. Figure 7Figures ad are the FESEM surface morphologies of G / VMT-PCNCs-0.1, G / VMT-PCNCs-0.2, G / VMT-PCNCs-0.3 and G / VMT-PCNCs-0.4, respectively. It was found that PCNCs connected the two-dimensional flaky vermiculite and guanine to form a large-area connected network structure. Due to the low content of PCNCs in G / VMT-PCNCs-0.1 and G / VMT-PCNCs-0.2, all guanine and vermiculite could not be completely connected, and some areas were not covered, exposing the polyethersulfone membrane at the bottom. Figure 7 Figure e shows that a large number of hollow guanine nanotubes are formed under the confinement of vermiculite, and the vermiculite flakes break and fall during the pyrolysis process ( Figure 7 (f) Most of the guanine nanotubes are attached to the vermiculite sheets. As the broken vermiculite sheets fall off, they form a porous three-dimensional network structure through the connection of PCNCs. A smaller number of guanine nanotubes are scattered outside the vermiculite sheets or combined with the flexible network structure of PCNCs.

[0067] At the same time, AFM and TEM were used to analyze the two-dimensional layer structure of vermiculite and guanine nanosheets and the one-dimensional structure of hollow guanine nanotubes and PCNCs. Figure 8 In (a, b), vermiculite flakes are stacked, with flexible guanine nanosheets and guanine nanotubes interspersed between the vermiculite flakes. Figure 8 Figure c is an AFM image of VMT-900, where it can be clearly seen that the surface of VMT is relatively smooth and flat. Analysis of the thickness of the VMT-900 flakes revealed that its thickness is about 1 nm, which is consistent with the thickness of the vermiculite nanosheets peeled off in the previous section, indicating that some samples may have broken off. Figure 8 Figure d is an AFM image of G / VMT-900, showing a large area of ​​guanine nanosheets covering the surface of the sheet with a porous structure. Analysis of the sheet size of the guanine nanosheets revealed that the thickness is about 1.2 nm and the pore size is about 30 nm. Some areas may be covered with vermiculite fragments, resulting in protrusions. Figure 8 f is the AFM image of G / VMT-PCNCs. It can be seen that in addition to PCNCs ( Figure 8 (e) In addition, there are large one-dimensional tubular structures around the vermiculite layer that are doped and connected with PCNCs. Combined with SEM image analysis, this one-dimensional tubular structure belongs to guanine nanotubes.

[0068] 2.5 Contact angle analysis

[0069] The change in the hydrophilicity of the membranes was analyzed by contact angle measurements. Fig. 9The water contact angles are all less than 90°, indicating that the membrane has good hydrophilicity, which is attributed to the hygroscopicity of vermiculite nanosheets and the hydrophilic groups of nanocellulose and guanine. The contact angles of G / VMT-PCNCs-0.1, G / VMT-PCNCs-0.2, G / VMT-PCNCs-0.3 and G / VMT-PCNCs-0.4 are 38.348°, 33.610°, 25.414° and 24.252°, respectively. As the amount of phosphorylated nanocellulose added increases, the contact angle decreases. It can be found that G / VMT-PCNCs-0.4 has the smallest contact angle and the strongest hydrophilicity.

[0070] 3. Chapter Summary

[0071] In summary, we used guanine as a precursor to prepare a "sandwich" structure of guanine / vermiculite composite ultrathin nanosheets in the confined space of vermiculite through a one-step pyrolysis method. Guanine formed one-dimensional carbon nanotubes and ultrathin two-dimensional nanosheets. By further introducing phosphorylated nanocellulose, guanine and vermiculite sheets were connected to form a three-dimensional network structure. A good one-dimensional structure can help fast and long-distance molecular and ion transfer, while the two-dimensional structure helps in-plane conduction. Under the joint action of hydroxyl, amine and phosphate groups, guanine / nanocellulose / vermiculite composite ultrathin nanosheets can conduct protons. Through SEM, AFM and other characterizations, it was found that the morphology of guanine can be regulated by adjusting the size of the interlayer space of vermiculite. The proton transfer behavior of the guanine / vermiculite nanosheet composite membrane was studied. At 25 ℃, when the relative humidity increased from 11% to 97%, the proton conductivity of the guanine / vermiculite composite material (G / VMT-900) pyrolyzed at 900 ℃ increased from 0.40 mS / cm to 0.50 mS / cm. After adding phosphorylated nanocellulose, the proton conductivity error of G / VMT-PCNCs decreased, and the proton conductivity increased with the increase of humidity. At 97%RH, as the temperature increased from 20 ℃ to 80 ℃, the proton conductivity of G / VMT-PCNCs increased to 1.15 mS / cm at the highest.

[0072] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. A method for preparing a guanine nanotube / vermiculite-phosphorylated nanocellulose composite material, comprising the following steps: (1) Preparation of guanine nanotube / vermiculite composites 1.1 Raw material pretreatment The raw vermiculite particles were ground and sieved to a particle size of 30-60 mesh, and then immersed in a hydrogen peroxide solution for 12-48 h. After filtering out the excess hydrogen peroxide solution, the vermiculite was heated in a microwave oven for 90 s. 1.2 Preparation of guanine nanotube / vermiculite ultrathin carbon nanosheets 0.5 g of pretreated vermiculite and 4.0 g of guanine were added to 50 mL of ultrapure water, mechanically stirred and mixed at 80 °C for 48 h, and then dried at 60 °C to obtain a mixture of pre-expanded vermiculite and guanine; the mixture was placed in a tube furnace, and under nitrogen protection, the mixture was heated from room temperature to 500-900 °C at a heating rate of 5 °C / min, and kept in the tube furnace for 1 h. After cooling to room temperature, the obtained guanine nanotubes / vermiculite ultrathin carbon nanosheets were ground into powder; (2) Preparation of guanine nanotube / vermiculite-phosphorylated nanocellulose composite membrane 3 g of microcrystalline cellulose and 24 g of urea were added to 16 g of phosphoric acid solution, and ultrasonicated at 80 °C for 5 h. The mixture was centrifuged at 11000 r / min for 15 min, the supernatant was removed, and the mixture was placed in a 150 °C oven for 25 min. Ultrapure water was added and centrifuged at 10000 r / min for 10 min. After repeated centrifugation and washing for 3 times, the pH was adjusted to 12, and ultrasonicated at 80 °C for 4 h. Finally, the phosphorylated nanocellulose PCNCs suspension was dialyzed with ultrapure water until the pH reached neutrality and diluted to 0.5 mg / mL. 5 mg of guanine nanotubes / vermiculite ultrathin carbon nanosheets were added to 0.1-0.4 mL of PCNCs suspension, then diluted to 100 mL with ultrapure water, filtered onto a 0.22 μm pore size polyethersulfone membrane under vacuum, and dried in an oven at 60 °C for 24 h to obtain a guanine nanotube / vermiculite-phosphorylated nanocellulose composite membrane.

2. The preparation method according to claim 1, characterized in that: The concentration of the hydrogen peroxide solution in step (1) is 30 wt %.

3. The preparation method according to claim 1, characterized in that: The concentration of the phosphoric acid solution in step (2) is 85 wt%.

4. A guanine nanotube / vermiculite-phosphorylated nanocellulose composite membrane prepared according to the preparation method according to any one of claims 1 to 3.

5. Use of the guanine nanotube / vermiculite-phosphorylated nanocellulose composite film according to claim 4 as a humidity sensitive material in a humidity sensor.